Factors associated with use of community-based, peer-led sexual and reproductive health services by adolescent boys and young men aged 18-24 in Lusaka, Zambia: A case control study nested in the Yathu Yathu trial. - Mwelwa M Phiri; Bernadette Hensen; Lucheka M Sigande; Sian Floyd; Albertus J Schaap; Melvin Simuyaba; Lawrence Mwenge; Rosemary Zulu-Phiri; Louis Mwape; Sarah Fidler; Musonda Simwinga; Richard Hayes; et al. (PLOS Global Public Health)
Introduction Adolescents and young people (AYP) aged 15-24 years have the least access to facility-based sexual and reproductive health (SRH) services, including HIV services. The Yathu-Yathu cluster-randomized trial (CRT) in Zambia tested whether a novel peer-led community-based approach increased knowledge of HIV status amongst AYP. In this nested case-control study, we aimed to identify factors associated with non-attendance to the Yathu Yathu hubs by adolescent boys and young men (ABYM) aged 18-24-years. Methods Yathu Yathu was a CRT conducted in two communities in Lusaka, Zambia, with 10 intervention and 10 control zones. AYP in all zones were offered prevention points cards (PPC), which incentivized and tracked service use at the hubs and health facility. In intervention zones, services were provided to AYP through community-based spaces (hubs) led by peer support workers. In these zones, cases were defined as those not having accessed any service at a hub and controls as those that accessed at least one service. Data were collected from October 2020 to January 2021 and analysed using methods appropriate for unmatched case-control studies. Results 161 cases and 160 controls consented to participate in the study. Participants aged 20-24 years (adjOR 1.99, 95%CI 1.26-3.12, p = 0.003), who were educated up to college level (adjOR 8.47,95%CI 2.08-34.53, p = 0.001) or who reported being employed in the last 12 months (adjOR 2.15, 95%CI 1.31-3.53, p = 0.002) were more likely to not attend the hubs. ABYM who had a friend with a PPC were more likely to attend the hubs (adjOR 0.18 95%CI 0.09-0.35, p<0.001). Most cases reported having their last HIV test at the local government health facility (58%) while most controls reported HIV-testing at a Yathu Yathu hub (82%). Among the controls, 84% (134/160) rated the hub experience as excellent. Among cases, 65% (104/161) stated they didn't visit the hubs "due to employment". Conclusions Despite Yathu Yathu services being community-based and more accessible compared to health facilities, we found age, education and employment were associated with not attending hubs. Strategies are needed to reach employed young men who may not have access to SRH/HIV services during conventional working hours and to better utilise peer networks to increase service use.